SAT0146 Single nucleotide polymorphisms in the TNF-α gene and efficacy of anticytokine therapy in patients with rheumatoid arthritis. (23rd January 2014) - Shkaruba, N.; Silkov, A.; Sennikova, J.; Sizikov, A.; Herzsog, O.; Dolgikh, S.; Mazurov, V.; Shulman, J.; Sizyakina, L.; Kalashnikova, T.; Kozlov, V.; Sennikov, S.
Abstract : Background: Tumour necrosis factor (TNF-α) is an multifunctional proinflammatory cytokine that plays an important role in systemic inflammatory process, autoimmune diseases and stimulates reactions of inflammation. There is increased level of TNF-α production in many systemic inflammatory processes. It is known that anti-cytokine therapy (infliximab, adalimumab) for rheumatoid arthritis neutralizes the effects of TNF-α. TNF-α is known to have some biallelic single-nucleotide polymorphisms that may associate with response to anti-TNF therapy. Objectives: The aim of this work was to examine the correlation of -1031T>C, -857C>T, -238G>A and -308G>A polymorphisms of the TNF-α gene with response to anti-TNF therapy with infliximab in patients with rheumatoid arthritis of the Southwest Siberian Population. Methods: Blood samples were taken from 91 patients with rheumatoid arthritis treated with infliximab. Patients with rheumatoid arthritis treated with infliximab were divided into responders and non-responders according to EULAR response criteria. Evaluation of treatment efficacy was conducted before the sixth infusion of the infliximab. The genetic distribution of SNPs in the promoter site was established by PCR-restriction fragment length polymorphism (PCRRFLP) analysis. For statistical analysis of the data we used the Spearman correlation index, χ 2 -criterion (Pχ) and Fisher's precise method for small samples. Results: The non-responders group was 21, 98%. It was found statistically significant association between the efficacy of therapy (EULAR response criteria) and the polymorphism at position -857C>T of the TNF-α gene before the sixth infusion of the infliximab. Spearman correlation index was for these parameters R = -0, 27 (p=0, 01). It was found that the CC genotype presented more frequently in non-responders (χ 2 =5, 27, p=0.02, OR=0.1, CI95 0.01272-0.7998). The risk of treatment failure in carriers of genotype -857CC increased by 29.29% compared with carriers of genotypes -857CT and -857TT. In addition it was found that C allele presented more frequently in patients with treatment failure (χ 2 =5, 015, p=0.03, OR=0.1851, CI95 0.04226-0.8103). The risk of treatment failure in carriers of allele C at position -857 was higher by 17.14% compared with carriers of the alternative allele. Conclusions: The polymorphism 857C>T is informative as a molecular marker of the efficacy of anti-TNF-α therapy of rheumatoid arthritis. Work is supported by grants of the RFBR (the grant 09-04-13620 ofi_s) and FTP "Scientific and Scientific-Pedagogical Personnel of the Innovative Russia in 2009-2013" (GC No. 02.740.11.0707). Disclosure of Interest: None Declared